2013
DOI: 10.1097/mao.0b013e3182877ef2
|View full text |Cite
|
Sign up to set email alerts
|

Usher Syndrome

Abstract: In this large series of patients with the diagnosis of US who have undergone cochlear implantation, CT and MRI imaging were normal. Significant delay in independent ambulation was present in this population secondary to abnormal vestibular function associated with US Type I. A majority of children developed significant open-set speech perception and oral communication skills. Implantation of US children provides them with the opportunity to develop useful hearing and oral communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…There is currently no cure for Usher syndrome. Standard management typically involves monitoring complications of RP and providing assistive hearing devices such as hearing aids or cochlear implants 40 . However, after previous demonstration of safety and efficacy in macaques, clinical trials for Usher syndrome type IB are underway that involve subretinal administration of UshStat® (EIAV-CMV- MYO7A ) (NCT01505062) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no cure for Usher syndrome. Standard management typically involves monitoring complications of RP and providing assistive hearing devices such as hearing aids or cochlear implants 40 . However, after previous demonstration of safety and efficacy in macaques, clinical trials for Usher syndrome type IB are underway that involve subretinal administration of UshStat® (EIAV-CMV- MYO7A ) (NCT01505062) 41 .…”
Section: Discussionmentioning
confidence: 99%
“…A multisite study of children receiving CIs from 1991 to 2010 identified 712 children; 26 (3.7%) of these children also had Usher syndrome type 1. 65 Mean time to follow-up was 7.8 (1–16) years. Speech perception outcomes for those with Usher syndrome indicated that 92% were able to achieve some level of open-set speech perception on age-appropriate tests and over half of these children were also oral communicators.…”
Section: Usher Syndromementioning
confidence: 99%
“…The costs of implants restoring vision are perhaps even higher. According to previous studies, a CI is an effective treatment in cases of deafblind patients with Usher syndrome (OMIM#276900) in terms of quality of life, verbal communication skills, and cognitive function [ 48 , 49 , 50 , 51 , 52 ]. The reports of the beneficial effects of CIs have also changed the practice of reimbursement, and a second CI could be reimbursed in adults in extraordinary cases.…”
Section: Discussionmentioning
confidence: 99%